Influence of depression literacy, mental health beliefs, and stigma on help-seeking behaviour : a semi-systematic review - Hazli Z,; Priyan R,; Gayatri G,; Sanjev PT,; Rashidi Mohamed Pakri Mohamed, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Despite having a mental health act and clinical practice guideline, Malaysian patients with depression frequently progress to severe disease with poor prognosis. Understanding the underlying factors which influence help-seeking behaviour using a patient journey approach can provide insights for designing effective interventions. The study aimed to determine the different stages of patients journey for depression including awareness, screening, diagnosis, treatment, adherence, and control using a semi-systematic review. The review was conducted through (i) structured keyword search in Embase, MEDLINE, and BIOSIS databases using OVID platform for English articles published between 2005 and 2021; and (ii) an unstructured search on websites of Google, Incidence and Prevalence Database, World Health Organization, and Malaysian Ministry of Health. Studies included in the semi systematic review were based on Malaysian patients aged ≥18 years at different journey stages for depression and publications from year 2005 to July 2021. Thesis abstracts, letters to the editor, editorials, and case studies, or articles representing smaller population subgroups were excluded. Three articles out of 1062 retrievals through structured search and two articles out of four retrievals through the unstructured search were included in the final synthesis. We have found that the prevalence of major depressive disease (2.3%), low initial screening (20%), diagnosis (50% to 60%) and adherence (30% to 40%), despite high awareness (76.9%) and initiation of treatment (75.3%). Low education level, ethnicity, stigma regarding mental health, and irrational prescription pattern of primary care physicians were associated with poor mental health help-seeking behaviour. Depression literacy can improve the help-seeking behaviour of the patients.